Olives for Your Florida Landscape - Mack Thetford; Jennifer L. Gillett-Kaufman; Michael J. Mulvaney (EDIS)
Olives have great potential as a landscape ornamental and may also provide opportunities for home fruit production. However, as a relatively new commercial crop to Florida, the cultural requirements of these trees are not completely known and research is ongoing to understand how to manage them for plant health and fruit yield as well as to make recommendations on varietal selections best suited to the southeastern region of the United States. This 5-page fact sheet includes culture and management information, selected references, and a table listing a selection of olive cultivars currently available in the U.S. It was written by Mack Thetford, Jennifer L. Gillett-Kaufman, Michael J. Mulvaney, and published by the UF Department of Environmental Horticulture, February 2015.